PENERAPAN GREEN ECONOMY DALAM KONSEP GANDENG-GENDONG DI KAMPUNG WISATA REJOWINANGUN, YOGYAKARTA - Ayunina Ciptantri Hadipranata , Qurrata; Setyowati, Hasanah (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
Yogyakarta as one of the tourism destination cities in Indonesia has a big role in the economic development. This involves tourism actors and all their activities. Several tourist villages in Yogyakarta carry out the concept of gandeng-gendong to support each other. The increase in tourism activities in these tourist villages raise problems that can affect the environment, for example: garbage and waste and lessen green areas. The Yogyakarta City Government must immediately find a solution to overcome this condition. This research was conducted to find out the application of green economy in the concept of gandeng gendong in Kampung Wisata Rejowinangun, Yogyakarta. This research used a descriptive qualitative method. In this study, sampling was carried out in Kampung Wisata Rejowinangun and data is obtained down to the level of clusters. The research conducted by interviews with related parties who were partners of gandeng gendong from Kampung Wisata Rejowinangun. A qualitative analysis model of Miles and Huberman was used to collect the data. The main finding of this research is that Kampung Wisata Rejowinangun has implemented a green economy with the concept of gandeng gendong, even though it is not comprehensively carried out yet.